(untitled) (Quinto Sol, 2018)
Recent historiography has analyzed political press in the 19th century as a political actor. In this framework, this article examines the links between the Legislative body, the Executive and the press in Mendoza between 1852 and 1880. It claims that they established a contesting dynamic over the control of public opinion, which was framed by the tension between the Legislative and the Executive. First, I review legislative projects to regulate the freedom of the press. Later, I analyze certain moments of political tension when the relations between the Legislature and the newspapers showed special virulence. For that, I study the minutes, bills, and documents exchanged between the Executive and the Legislative, as well as the Official Register and newspapers articles.